ENHANCEMENT OF FETAL ECG SIGNAL USING ADAPTIVE NOISE CANCELLATION - KIRUTHIGA.G, SHARMILA.A; MAHALAKSHMI.P (International Journal of Pharma and Bio Sciences, 2015)
Fetal heart rate monitoring yields vital information about the fetus health and can support medical decision making in critical situations. The Fetal Electro Cardio Gram (FECG) signal reflects the electrical activity of the fetal heart. It contains information about the health status of the fetus, so that an early diagnosis of any cardiac defects before delivery increases the effectiveness of the appropriate treatment. A compound signal is obtained non-invasively by placing electrodes on the abdominal area of the mother which comprises of both maternal as well as fetal ECG signals contaminated by various other signals from a the body and externally induced noises. This paper represents the enhancements achieved by the application of adaptive filtering technique using MATLAB. The characteristics of the FECG signal were shown and a relatively clean FECG signal is obtained.